Analysis of the Mechanism of Gram Differentiation by Use of a Filter-Paper Chromatographic Technique - Bartholomew, J. W. (1965)
Bartholomew, J. W. (University of Southern California, Los Angeles), Thomas Cromwell, and Richard Gan. Analysis of the mechanism of Gram differentiation by use of a filter-paper chromatographic technique. J. Bacteriol. 90:766–777. 1965.—Data are presented which demonstrate that the mechanism of gram-positivity could not be due solely to factors such as a single, specific gram-positive substrate, specific affinities of crystal violet for certain cellular components, a specific crystal violet-iodine-substrate complex, or to any specific characteristic of the dye, iodine, or solvent molecules. Ruptured cells of gram-positive organisms stain gram-negatively when subjected to a standard Gram-stain procedure. However, when stained fragments of broken cells were deposited in thick layers on the surface of filter-paper strips and exposed to decolorizers, the rate of dye release correlated with the Gram characteristic of the intact cell. Therefore, the intact cell in itself is not an absolute requirement for Gram differentiation. The data are interpreted as indicating that the mechanism of Gram differentiation primarily involves the rate of permeation of molecules (dye, iodine, solvent) through the interstitial spaces of cell-wall material.